Severe methotrexate toxicity in elderly patients under diuretics - Martin Aringer; Nicolai Leuchten; Kristine Herrmann; Cara Kumar; Matthias Kuhn (RMD Open)
Objectives To explore the toxicity of low-dose methotrexate (MTX), an uncommon, but life-threatening event.Methods We analysed the presentation, course and risk factors of all patients admitted to the rheumatology ward with severe low-dose MTX toxicity. These patients were compared with patients without signs of relevant MTX toxicity.Results The 12 patients admitted for MTX toxicity included 7 patients with rheumatoid arthritis, 2 with psoriatic arthritis or psoriasis, 2 patients with giant cell arteritis and 1 with myositis. 1 patient died from infections, while 11 survived under folinic acid administration. All patients suffering from severe MTX toxicity were older than 70 years and were therefore compared with 400 patients who were also older than 70 years, but without MTX toxicity. Of these 400 control patients, the group of patients not on MTX (n=232) had more renal impairment than the group of patients on MTX (n=168). Compared with the 168 MTX-treated patients without toxicity, the 12 patients with life-threatening toxic events had a lower median estimated glomerular filtration rate (eGFR) at the routine visit preceding the acute event (64 (range 32–77) vs 69 (range 8 to >90) mL/min x 1.73, p=0.0251). A multivariate analysis found that patients with toxicity were more frequently treated with diuretics (6/12 vs 24/168), proton pump inhibitors (PPIs; 10/12 vs 70/168) and levetiracetam (2/12 vs 1/168).Conclusions Patients older than 70 years with lower eGFR and being on diuretics, but also on PPIs and levetiracetam, have a significantly higher risk for MTX toxicity.